Professional development within theEffective Early Learning Programme: a contribution to a participatory and context-sensitive approach to ECEC evaluation - Barros Araújo, Sara (2018)
This paper aims to describe and analyse a case study on professional development that was centred on the Effective Early Learning (EEL) Programme. This process was a part of a larger dissemination project of the EEL programme nationwide, designed to train specialised facilitators at a local level who could, in turn, support the professional development of their peers. From a theoretical stance, it focuses on a democratic and participatory approach to the evaluation and development of quality in ECEC contexts. The study involved the participation of 12 pre-school teachers and a specialised trainer. Results show perceived effects of the process of staff development on professional learning at the level of observation skills, reflection-on-action and critical insertion. Also, the participants recognised that experimentation in practice contexts and shared reflection were the most meaningful and facilitative strategies in their learning.